Molecular imaging of macrophage protease activity in cardiovascular inflammation in vivo - Quillard, Thibaut; Croce, Kevin; Jaffer, Farouc A.; Weissleder, Ralph; Libby, Peter (Thrombosis and Haemostasis, 2011)
Macrophages contribute pivotally to cardiovascular diseases (CVD), notably to atherosclerosis. Imaging of macrophages in vivo could furnish new tools to advance evaluation of disease and therapies. Proteolytic enzymes serve as key effectors of many macrophage contributions to CVD. Therefore, intravital imaging of protease activity could aid evaluation of the progress and outcome of atherosclerosis, aortic aneurysm formation, or rejection of cardiac allografts. Among the large families of proteases, matrix metalloproteinases (MMPs) and cysteinyl cathepsins have garnered the most interest because of their participation in extra-cellular matrix remodelling. These considerations have spurred the development of dedicated imaging agents for protease activity detection. Activatable fluorescent probes, radiolabelled inhibitors, and nanoparticles are currently under exploration for this purpose. While some agents and technologies may soon see clinical use, others will require further refinement. Imaging of macrophages and protease activity should provide an important adjunct to understanding pathophysiology in vivo, evaluating the effects of interventions, and ultimately aiding clinical care.
Keywords: Proteases; imaging; macrophage